Pulmonary Blastoma: A Case Report and Review of the Literature - Haseeb Ahsin; Farwa Aftab; Alishba Amjad; Sumbal Saeed; Fattahullah Khan (Clinical Case Reports)
ABSTRACT This report aimed to underscore the significance of pulmonary blastoma, a rare entity with limited literature, by contributing insights into its clinical features, diagnostic approaches, and treatment modalities. Additionally, it emphasizes the critical role of a multidisciplinary approach in the effective management of this complex and challenging disease.